Labor markets, gender and social stratification in East Asia : a global perspective - Tarōmaru, Hiroshi, 1968- (Intimate and the public in Asian and global perspectives, 2016)
Following the Asian economic crisis of the 1990s, this is the first book to examine the structure and transformation of the labor markets and social stratification of contemporary East Asia, namely Japan, Korea, Taiwan, and China, focusing in particular on gender inequality. It deals with social mobility and gender differences in unemployment, temporary employment and self-employment. Additionally, gender segregation, social identity and suicide rates are also addressed. Taken together, the issues raised in this volume reinforce the advantage of a comparative approach to East Asian Studies. The findings, supported by strong statistical analysis, clearly call into question a longstanding view that East Asian gender regimes and class structure are homogeneous. Indeed, this is demonstrably not the case, as Labor Markets, Gender and Social Stratification in East Asia shows, revealing as it does considerable diversities in labor markets, gender regimes, and social mobility within East Asian societies due to historical and institutional differences. Contributors include: Chang Chin-Fen, Kim Young-Mi, Oda Akiko, Phang Hanam, Sakaguchi Yusuke, Shibata Haruka, Takamatsu Rie, Takenoshita Hirohisa, Tarohmaru Hiroshi, Xie Guihua, and Yamato Reiko.